2015
DOI: 10.1007/s00267-015-0482-4
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Characterizing Forest Areas with High Societal Values: Experiences from the Pacific Northwest of USA and Central Europe

Abstract: In recent decades, much work has been invested to describe forest allocations with high societal values. Yet, few comparative analyses have been conducted on their importance and differences across the regions of the globe. This paper introduces a conceptual framework to characterize forest priority areas defined as areas with identified higher importance of societal values in the context of multi-objective forest management. The six dimensions of the framework (designation objective, prioritization of objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It has been argued that if non-timber services are part of a timber management plan on the majority of the forestland, there may be a lesser need for segregating or prioritizing objectives in different areas [131]. However, in a region where small private properties dominate, the diversity of forest services must often be packed into small woodlot areas, which makes integration of intensive forestry (plantations) often incompatible with other services [131].…”
Section: Zoning Scenarios For the St-benoî T-du-lac Abbey Propertymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been argued that if non-timber services are part of a timber management plan on the majority of the forestland, there may be a lesser need for segregating or prioritizing objectives in different areas [131]. However, in a region where small private properties dominate, the diversity of forest services must often be packed into small woodlot areas, which makes integration of intensive forestry (plantations) often incompatible with other services [131].…”
Section: Zoning Scenarios For the St-benoî T-du-lac Abbey Propertymentioning
confidence: 99%
“…However, in a region where small private properties dominate, the diversity of forest services must often be packed into small woodlot areas, which makes integration of intensive forestry (plantations) often incompatible with other services [131]. Integration of timber objectives in high conservation value areas may also be incompatible with biodiversity protection objectives [131].…”
Section: Zoning Scenarios For the St-benoî T-du-lac Abbey Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…The association further highlights the importance of a common language, which can be achieved by the ESS approach. Simoncic et al (2015) [33] identified the consideration of diverse societal values as a challenge in forest planning for many years. The authors mention the spatial classification of forest areas as a possible solution to this problem.…”
Section: Introductionmentioning
confidence: 99%
“…This work could also serve as a basis for future forest ecosystem accounting studies and reporting commitments in the forest sector. Since FFM is well-established in Central European forest authorities and the German FFM guidelines have already proved to provide a valuable basis for international comparative purposes [33], we use the German FFM approach as a starting point. Therefore, one core element of this research is the harmonisation of German FFM state guidelines and the federal guideline with each other.…”
Section: Introductionmentioning
confidence: 99%